Caracterização fenotípica de células mononucleares sanguíneas de pacientes com periodontite crônica - NASCIMENTO, Johnny Ramos do (2015)
Introduction: Chronic periodontitis is an infectious inflammatory disease from dental protecting and supporting tissues. Its final stages is tooth loss. Studies have shown that the type of host immune response and the kind of immune cells involved, such as, macrophages and T lymphocytes, can influence and change disease progression. Despite its restriction to periodontal tissue and its association to other diseases, the systemic effects of chronic periodontitis on immune cells are still not clear. Objective: The aim of this study is to characterize the phenotypical profile of peripheral blood mononuclear cells (PBMC) from the individuals with chronic periodontitis. Patient and Methods: It is a cross-sectional study with chronic periodontitis patients, treated at the Periodontitis Clinic of UFMA Dentistry Course. The Ethics Committee of UFMA approved the project and all the patients were aware of the research and signed the TCLE. Two groups were established: the control group (GC)(n=22), with healthy individuals and no trace of chronic periodontitis, and the group of chronic periodontitis patients (GPC)(n=26) with no systemic alterations. Blood samples were collected (4 mL) to obtain plasma to perform the IL-2, IL-4, IL-6, IL-10, IFN-, TNF- and IL-17A cytokines dosage, through CBA method. For immunophenotyping, PBMC were obtained through Ficoll-Paque™ PLUS density gradient solution method. For phenotyping of monocytes, B lymphocytes and T lymphocytes, the PBMC were counted, adjusted and abeled with the following monoclonal antibodies conjugated with fluorochromes: anti-CD3 and anti-CD14 conjugate with FITC; anti-CD4, anti-CD25, anti-CD14 and anti-HLA-DR conjugated with PE e anti-CD19, anti-CD86, anti-CD8 and anti-CD4 conjugated with PerCP (BD Biosciences-Pharmingen). Samples were acquired in cytometer (BD FACSCalibur - BD Biosciences) and analyzed in FCAP ARRAY software Version 3.0 and Version 9 FlowJo (TreeStar). Results: There was an increase of total T lymphocytes (CD3+) as well as helper T lymphocytes (CD3+/CD4+) cells and activated helper T lymphocytes (CD3+/CD4+/CD25+) on the GPC, compared to the GC. There was also an increase in the number of monocytes (CD14+), as well as, antigen presenting monocytes (CD14+/HLADR+/CD86+) when compared to the control group. There was no statistical difference between the GC and GPC in the number of B lymphocytes (CD19+) and cytotoxic T lymphocytes (CD3+/CD8+). There was no difference in dosage of cytokines of profiles Th1/Th2/Th17 between groups. Conclusion: Chronic periodontitis, a local infectious inflammatory disease, can cause changes in the number of circulating monocytes and helper T lymphocytes and induce its activation, but these changes do not seem to reflect on the systemic cytokine profile